Density Functional Study of Cubic, Tetragonal, and Orthorhombic CsPbBr(3) Perovskite - Ghaithan, Hamid M. (ACS Omega, 2020)
[Image: see text] Cesium lead bromide (CsPbBr(3)) perovskite has recently gained significance owing to its rapidly increasing performance when used for light-emitting devices. In this study, we used density functional theory to determine the structural, electronic, and optical properties of the cubic, tetragonal, and orthorhombic temperature-dependent phases of CsPbBr(3) perovskite using the full-potential linear augmented plane wave method. The electronic properties of CsPbBr(3) perovskite have been investigated by evaluating their changes upon exerting spin-orbit coupling (SOC). The following exchange potentials were used: the local density approximation (LDA), Perdew–Burke–Ernzerhof generalized gradient approximation (PBE-GGA), Engel–Vosko GGA (EV-GGA), Perdew–Burke–Ernzerhof GGA revised for solids (PBEsol-GGA), modified Becke–Johnson GGA (mBJ-GGA), new modified Becke–Johnson GGA (nmBJ-GGA), and unmodified Becke–Johnson GGA (umBJ-GGA). Our band structure results indicated that the cubic, tetragonal, and orthorhombic phases have direct energy bandgaps. By including the SOC effect in the calculations, the bandgaps computed with mBJ-GGA and nmBJ-GGA were found to be in good agreement with the experimental results. Additionally, despite the large variations in their lattice constants, the three CsPbBr(3) phases possessed similar optical properties. These results demonstrate a wide temperature range of operation for CsPbBr(3).